Efficient routing for wireless mesh networks using a backup path. (2nd May 2012) - Esmailpour, Amir; Nasser, Nidal; Dallal, Jehad Al
SUMMARY: Wireless mesh networks (WMNs) have a proven record in providing viable solutions for some of the fundamental issues in wireless networks such as capacity and range limitations. WMN infrastructure includes clusters of mobile ad‐hoc networks connected through a fixed backbone of mesh routers. The mesh network can be constrained severely because of various reasons, which could result in performance degradation such as a drop in throughput or long delays. Solutions to this problem often focus on multipath or multichannel extensions to the existing ad‐hoc routing protocols. In this paper, we propose a novel solution by introducing an alternative path to the mesh backbone that traverses the mobile ad‐hoc networks part of the WMN. The new routing solution allows the mobile nodes (MNs) to establish direct communication among peers without going through the backbone. The proposed alternative ad‐hoc path is used only when the mesh backbone is severely constrained. We also propose, for the first time in WMNs, using MNs with two interfaces, one used in the mesh backbone communication and the other engaged in the ad‐hoc network. A scheme is presented for making the MN aware of link quality measures by providing throughput values to the ad‐hoc on‐demand distance vector protocol. We use piggybacking on route reply messages in ad‐hoc on‐demand distance vector to avoid incurring additional costs. We implemented our solution in an OPNET simulator and evaluated its performance under a variety of conditions. Simulation results show that the alternative ad‐hoc path provides higher throughput and lower delays. Delay analysis show that the throughput improvement does not impose additional costs. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : A novel solution by introducing an alternative path to the mesh backbone that traverses the mobile ad hoc networks part of the WMN is proposed in this paper. The new routing solution allows the mobile nodes to establish direct communication among peers without going through the backbone. Finding results show that the alternative ad hoc path provides higher throughput and lower delays. Delay analysis shows that the throughput improvement does not impose additional costs.